(untitled) (BIS Humanities and Social Science, 2026)
The proliferation of smartphone use among adolescents has raised concerns about its psychological and ethical implications. While research has established links between smartphone addiction and moral disengagement, the underlying mechanisms and protective factors remain underexplored. This study examines whether self-control mediates the relationship between smartphone addiction and moral disengagement, and whether mindfulness moderates this mediation pathway. A cross-sectional survey was conducted with 294 high school students from three public high schools in Surakarta, Indonesia, selected through stratified cluster random sampling. Data were analyzed using Structural Equation Modeling-Partial Least Squares to test the moderated mediation model. The structural model demonstrated good fit and explained substantial variance in moral disengagement. Smartphone addiction showed a significant strong direct effect on moral disengagement, indicating its influence operates predominantly through direct pathways. Additionally, smartphone addiction significantly reduced self-control, which in turn significantly increased moral disengagement, confirming partial mediation through the self-regulatory mechanism. The presence of both direct and indirect effects suggests that smartphone addiction influences moral disengagement through multiple pathways. Notably, mindfulness significantly enhanced self-control, demonstrating its role as a protective factor in strengthening self-regulatory capacities. However, mindfulness did not significantly moderate the smartphone addiction-self-control relationship, whereby the negative effect of smartphone addiction on self-control remained consistent across different levels of mindfulness. This study advances understanding of how smartphone addiction leads to moral disengagement by identifying self-control as a key mediating mechanism and mindfulness as an important factor that directly enhances self-regulatory capacity.